Rise in arsenic pollution and oral cancer: A call for action - Amol S. Dhane; Sachin C. Sarode; Gargi S. Sarode; Nilesh Kumar Sharma (Oral Oncology Reports)
Over 140 million individuals across 70 countries have been exposed to arsenic with the levels surpassing World Health Organization guidelines. Epidemiological evidence strongly supports a causal relationship between oral cancer and arsenic, necessitating stringent regulatory policies and public health initiatives. This commentary delves into the carcinogenic qualities of arsenic, specifying its interference with vital biological functions and its role in promoting cancer development and progression. Regional disparities in oral cancer incidence are linked to varying levels of arsenic exposure, predominantly in areas with contaminated water sources. The challenges in prevention and advocates efficient screening, awareness campaigns, and long-term arsenic remediation are the need of the hour. Despite scientific controversies surrounding the linkage of arsenic with oral cancer, the overwhelming evidence demands coordinated action to combat arsenic contamination and its severe oral health consequences. We also discussed the therapeutic potential of arsenic in oral cancer. Future research is proposed to investigate the molecular role of arsenic in gutkha and tobacco users, considering its contribution to oral cancer heterogeneity.